ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI PROFITABILITAS BANK PERKREDITAN RAKYAT DI KABUPATEN BADUNG - Sri Agustini, Si Luh Anik; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi, 2014)
The purpose of this study was to determine the effect of CAR, LDR, and NPL on profitability. Return on Assets (ROA) ratio is one that can be used to measure and compare the profitability performance. Measurement of the effectiveness of the company by utilizing its assets to gain an advantage reflected in ROA. Population during the years 2010-2012 as many as 52, with a purposive sampling method. Based on the defined criteria, the obtained 31 samples that meet the criteria, the number of 93 observations. By using a multiple linear regression analysis technique, the results obtained that CAR has a positive effect on ROA, LDR has a positive effect on ROA and NPL negative effect on ROA.
Keywords: CAR, LDR, NPL, ROA